(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The concept of using a card for purchases was described in 1887 by Edward Bellamy in his utopian novel Looking Backward. Bellamy used the term credit card eleven times in this novel, although this referred to a card for spending a citizen’s dividend rather than borrowing. It was first used in the 1920s, in the United States; the design of the credit card itself has become a major selling point in recent years. The value of the card to the issuer is often related to the customer’s usage of the card, or to the customer’s financial worth. This study attempts to identify the factors influencing credit cards usage in Private Sector Banks as well asgender wise opinion regarding credit card in Private Sector Banks. Finally, is to identify the satisfaction level of credit card users and also examine the risk tolerance of credit card users in Private Sector Banks. Data has been collected from 110 respondents from the study area. Convenience sampling method is used while selecting the samples.Tools and techniques- F Statistics, ‘t’ Statistics, Percentage,Rankis used for this paper work.